Sujeitos do património: os novos horizontes da museologia social em São Brás de Alportel - Lorena Sancho Querol; Emanuel Sancho (e-cadernos ces)
The words museology and museum reveal different textures, nuances and meanings when understood through the perspective of museology committed to sustainable development. “A museology of inclusive nature” or a Social Museology then emerges, whose participatory practices can be translated into the recognition of other agents, other heritages, other aspects of local culture.This article depicts the experience of a museum in the Algarve (Portugal) committed to this cause, the Costume Museum of São Brás de Alportel. Its management model, marked by the search for sustainability, the freedom of action and sharing that results from the recognition and definition of new uses of local knowledge and experiences, is based on the existence of “action layers” that allow us to reposition museology and the museum at the wake of the construction of an alternative globalization.